Man, Nature and Society in Selected Works of Frederick Philip Grove and Thomas Hardy - Reynolds, Henry Robert (My University, 1974)
The first chapter of this thesis is directed toward Grove's and Hardy's view of man in their novels. After reading the major works of both writers the conclusion put forward here is that neither Grove nor Hardy is willing to write a novel that ignores the possibility of suffering. They do not, however, look upon suffering as the focal point of life. Essentially they direct their attention to man's unique capacity to adapt continually to new, and often difficult, situations. The misfortunes that confront both writers' characters are aimed at showing the reader a variety of consequences for particular patterns of action. There are no guarantees of happiness, but for both writers man is not meant to suffer either irrationally or passively. The freedom to act is an essential part of his character and, as such, he must continually exercise his freedom of choice. For both Grove and Hardy it is this individual freedom to choose, to redefine one's self and one's situation, that enables man to discover and maintain some degree of happiness in life. Similarly, it is this individual freedom, to act that allows all men the chance to discover the profound and the tragic proportions that lie within the human spirit.
Both writers locate their characters in settings that are never too removed from the demands of a force that may generally be called Nature. Often the demands of this external force are beyond the intellectual scope and physical strength of men. The suffering that results from the confrontation between Nature and man would seem to indicate that man is destined to suffer irrationally. The conclusion that is made in the second chapter of this thesis, however, is that both Grove and Hardy appear to believe that man must use Nature's laws as co-ordinates that place him in Nature and, at the same time, above it. Both Grove and Hardy repeatedly illustrate that man is more than just a receptor of Nature's fury. He is also a recorder or focal point of Nature's order. Both Grove and Hardy show that man can use his unique relationship with Nature to discover toleration and understanding.
Both writers also use the simplicity of rural order and the demands of more complex urban social beliefs as guidelines against which the actual needs of individual men may be measured. Grove and Hardy appear to support a belief in the individual's right to test the validity of any social structure. Similarly, both writers illustrate that the demands of society, like the demands of Nature, are external requirements that test individual men. The conflict that arises as a result of the confrontation of man and society is an integral part of both writers' approach to an appraisal of the freedom of individual men. The final chapter of this thesis, then, concludes with the belief that neither writer sides for or against a particular view of society, but both writers do side with man's right to discover from society a more accurate understanding of individual needs and characteristics.
Keywords: English; English Language and Literature; English Language and Literature